Partisipasi politik atau sekadar formalitas: Mengkritisi demokrasi modern di Indonesia - Annan, SHOHIBBUL BAHRI (Maliki Interdisciplinary Journal, 2026)
This study examines the phenomenon of political participation in modern Indonesian democracy, which tends to be trapped in procedural and formalistic aspects. High voter turnout does not necessarily reflect substantive democratic quality when it is not accompanied by critical awareness, political understanding, and civic responsibility. This research employs a qualitative method with a literature study approach by analyzing various references, scientific journals, official documents, and academic studies related to democracy and political participation. The findings reveal that pseudo-participation appears in voting behavior without understanding candidates’ visions, missions, and track records. This phenomenon is influenced by low political literacy, the dominance of social media that creates echo chambers, and money politics that fosters transactional relationships between voters and candidates. The resulting impacts include the emergence of procedural democracy, declining public trust in state institutions, and weakening governmental integrity. To address these issues, transformation toward deliberative democracy is required through strengthening political education, improving digital literacy, and revitalizing the culture of deliberation in the public sphere. Therefore, democratic quality should not only be measured by the number of participants in elections, but also by the level of citizens’ awareness in making rational and responsible political choices for the common good.